Should thread-embedding and auricular acupuncture be combined rather than used individually for non-specific chronic low back pain?: A double-blinded, randomized, sham-controlled trial - Thuy-Tu Long Pham; Nam Trung Le; Tin Trong Nguyen; Haoran Chu (Integrative Medicine Research, 2025)
Background: Non-specific chronic low back pain (NCLBP), the most common type, is a leading cause of global disability. The combined effect of thread-embedding acupuncture (TEA) and auricular acupuncture (AA) remains unclear. This study evaluates whether combining TEA and AA improves NCLBP management compared to either alone. Methods: In this double-blind randomized controlled trial, 168 NCLBP patients were randomized into four groups (n = 42): TEA+AA, TEA+sham AA, AA+sham TEA, or sham both, alongside conventional treatment. The intervention lasted 4 weeks with a 4-week follow-up. The primary outcome was the Oswestry Disability Index (ODI); secondary outcomes included pain score, paracetamol use, quality of life, global improvement, and adverse events (AEs). Results: In the intention-to-treat analysis, the acupuncture groups showed significantly lower ODI percentage scores compared to the sham group (p < 0.0001). Both the TEA+AA and TEA+sham AA groups outperformed the AA+sham TEA group (mean differences [MD]:9.1 and -7.5, respectively; p < 0.0001) at week 4 and achieved the minimal clinically important difference (MCID) during follow-up. The TEA+AA group showed greater improvement than the TEA+sham AA group at weeks 2 and 6; however, these differences did not reach the MCID. Secondary effectiveness outcomes followed a similar trend. The results were consistent with the per-protocol analysis. AEs were mild and self-limiting. Conclusion: TEA and AA are safe and effective adjuncts for managing NCLBP, with TEA showing more sustained benefits. Adding AA into TEA may accelerate response, though clinical relevance remains uncertain. Further multicenter studies with longer follow-up and syndrome-based approaches are warranted. Trial registration: ClinicalTrials.gov (NCT06682273).